PENGARUH PENGALAMAN KERJA, PRESTASI KERJA DAN PELATIHAN TERHADAP PENGEMBANGAN KARIER KARYAWAN - Adnyani, Ni Luh Putu Ria; Dewi, A.A.Sagung Kartika (E-Jurnal Manajemen; Vol 8 No 7 (2019)DO - 10.24843/EJMUNUD.2019.v08.i07.p03, 2019)
This study aims to determine the effect of work experience, work performance and training on career development. This research was conducted in Wapa at Ume Resort & Spa. The number of samples used is 75 employees, with the saturated sample method where all population numbers are sampled. Data collection was obtained from interviews and questionnaires. The analysis technique used is multiple linear regression analysis. The results of this study found that work experience has a positive and significant effect on career development, work performance has a positive and significant effect on career development and training has a positive and significant effect on career development. To improve career development, the company needs to pay attention to the work experience of employees so that employees are able to complete and be responsible for the tasks assigned smoothly. The company must pay attention to the cooperation carried out by employees in order to be able to create good cooperation with colleagues and superiors, so that with good cooperation can facilitate the work. Keywords : work experience, work performance, training, career development